2001
DOI: 10.1046/j.1537-2995.2001.41010056.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ABO blood groups on primary hemostasis

Abstract: Significant ABO-group-specific differences in nonvascular primary hemostasis could be found by IVBT. The differences are small, however, and lie within the normal range. Whether these differences have any biologic relevance can only be speculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
69
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 38 publications
4
69
0
Order By: Relevance
“…[24][25][26] The local and systemic effects of long-and short-term ASA therapy have extensively been investigated. [4][5][6][7]12,13 New antithrombotic agents, like thienopyridines, have recently been developed but lack long-term follow-up results and data concerning intra-and interindividual variability. In order to guarantee optimal secondary prophylactic therapy for the prevention of vascular events after PTA, a test for monitoring antiplatelet therapy, especially for detecting 'non-responders ' would be favorable.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] The local and systemic effects of long-and short-term ASA therapy have extensively been investigated. [4][5][6][7]12,13 New antithrombotic agents, like thienopyridines, have recently been developed but lack long-term follow-up results and data concerning intra-and interindividual variability. In order to guarantee optimal secondary prophylactic therapy for the prevention of vascular events after PTA, a test for monitoring antiplatelet therapy, especially for detecting 'non-responders ' would be favorable.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the last decade, the interest of PFA-100 has often been called into question, since, although its sensitivity appears to be high, its specificity is low and includes a number of factors that may modify the results [10,11]. A metaanalysis has shown the system to be successful in detecting VWD [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been consistently found that individuals with the O blood group have lower vWF levels on average than individuals with other blood groups, although the mechanism by which this occurs is unclear. Some studies (Moeller et al, 2001) have suggested that the ABO antigens influence the rate of proteolysis or clearance of the vWF molecule.…”
Section: Introductionmentioning
confidence: 99%